Of courtiers and kings : the biblical Daniel narratives and ancient story-collections - Holm, Tawny, 1966- (Winona Lake, Indiana : Eisenbrauns, 2013)
Holm$1 (Bs book is an innovative approach to the biblical Book of Daniel. It places Daniel against the background of story-collections, an ancient genre that began in Egypt in the mid-second millennium B.C.E. This work focuses on Daniel 6-4 and provides detailed comparisons with specific bodies of story-collections and other related material from the Ancient Near East. In this regard, special attention is given to Egyptian court tales, a large corpus mostly neglected by previous biblical scholars. Thus, this book brings new evidence and fresh insights to the field of Daniel studies, which in recent years has generated constant interest, especially as it pertains to textual issues and literary matters. --s
Introduction -- The Story-Collection Genre: Survey and Prospect -- The Story-Collection and Related Material in Antiquity -- The Book of Daniel in Light of the Story-Collection Genre -- The Book of Daniel in Light of Ancient Near Eastern Story-Collections and Related Material -- Conclusions.
Includes bibliographical references and indexes.
Online resource; title from PDF title page (ebrary, viewed November 6, 2013).
Master record variable field(s) change: 650
Keywords: Bible. -- Criticism, interpretation, etc; Bible; Short stories; Short stories, Egyptian; RELIGION -- Biblical Studies -- Prophets; Short stories; Electronic books; Criticism, interpretation, etc